Analysis of Obstacles in Supervision of Value Added Tax Collectors on Trading Through Electronic Systems (E-Jurnal Akuntansi, 2026)
The Directorate General of Taxes (DGT) made a change to the duty and function of the supervision of KPP Badan dan Orang Asing (Badora) to supervise the business actors of Trading Through Electronic Systems (TTES). This research aims to analyze the obstacles faced by Account Representatives (AR) at KPP Badora in supervising TTES VAT collectors using the ADKAR model. A case study approach with mixed methods was employed in this research, with data collected through questionnaires and interviews. The results showed that ARs experienced obstacles in supervising TTES VAT collectors based on the ADKAR model. While no obstacles were identified in the aspects of awareness and desire, challenges were evident in the aspects of knowledge, ability, and reinforcement. In the knowledge aspect, ARs lacked a comprehensive understanding of the business processes of TTES VAT collectors. In the ability aspect, obstacles included the absence of comparative data on transaction values and traffic volume, an insufficiently supportive supervisory information system, and unenforceable sanctions. Finally, in the reinforcement aspect, ARs were not supported by a supervisory business process tailored to the specific characteristics of TTES VAT collectors.
Keywords: Account Representative; ADKAR; Suprvision; VAT; TTES